Ecological risk of microplastic toxicity to earthworms in soil: A bibliometric analysis - Guo, Sen; Wang, Qiong; Li, Zishuang; Chen, Yanhua; Li, Hongjie; Zhang, Jiajia; Wang, Xuexia; Liu, Jiawei; Cao, Bing; Zou, Guoyuan; Zhang, Baogui; Zhao, Meng (Frontiers in Environmental Science, 2023)
Accumulation of microplastics (MPs) in soil is a serious environmental concern. Addition of exogenous MPs can alter structure and physicochemical properties of and material transport in soil. MPs are particularly toxic to earthworms, which are soil ecosystem engineers, and exacerbate ecological risks; however, there is a lack of comprehensive and in-depth analyses of how MPs exhibit toxicity to/towards earthworms. In this study, we report a bibliometric analysis of 77 peer-reviewed papers published before December 2021 to systematically analyze how the addition of exogenous MPs contributes to earthworm toxicity and clarify the historical development and research hotspots in this field. We found that first, polyethylene and polystyrene are the most common materials used to study the toxic effects of MPs on earthworms. Second, the toxic mechanisms of MPs on earthworms mainly involve histopathological damage and oxidative stress, as well as serving as carriers of complex pollutants (e.g., heavy metals and organic pollutants) through combined adsorption–desorption. Third, oxidative stress is the typical reaction process of MPs toxicity in earthworms. When the content of MPs in soil exceeds 0.1%, earthworm growth is affected, and oxidative stress is induced, resulting in neural and DNA damage. Based on published studies, the prospects for future research on the ecological risks posed by MPs to earthworms have also been discussed. Overall, our findings help clarify the ecological risk of soil MPs toxicity to earthworms, reveal the mechanism of their toxic effects, and provide a theoretical basis for future studies focusing on establishing a healthy and ecologically sustainable soil environment.